KEBIJAKAN PERTANGGUNGJAWABAN PIDANA OLEH PELAKU KEJAHATAN TERHADAP HARTA BENDA ( STUDI KASUS TERHADAP RECIDIVIS ) - Dian Puspita Evariani, Eko Soponyono, Sularto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Law enforcement is a legal certainty that promotes excessive legisme view, a constraint entry legal principles and values (justice) who want to uphold the law in court. Law enforcement to ignore the value of justice can affect the image of the legal and law enforcement in the public eye. Policies regarding the criminal responsibility of judges in decisions on PN Semarang what recidivis in accordance with the rules of the Penal Code governing recidive or even seen a case with more discretion. The problem is how the policy of criminal responsibility by judge recidivis in the present and how the settings in the future. This thesis first discusses the policies of criminal responsibility by perpetrators of crimes against property especially recidivis theft relating to the setting of the Criminal Code. Second, the concept of repetition in settings offender Criminal Code of 2012.